Analysis of Criminal Law Reform in Eradicating Corruption in the Future - Nadia Mahza Prameswari (Proceeding of the International Conference on Law and Human Rights, 2024)
Extraordinary crimes such as corruption have a wide impact on the political, economic, and social sectors, so that eradicating them is a top priority for the Indonesian government. The government has established various policies to combat corruption, one of which is through Law No. 31 of 1999 which was amended to Law No. 20 of 2001. However, the implementation of this law has not been optimal, with many corruption cases that have not been handled and inadequate recovery of state financial losses. To overcome this, the government has reformed the criminal law through Law No. 1 of 2023 concerning the Criminal Code (KUHP), which is expected to provide a deterrent effect and recover state losses. This paper analyzes the reform of criminal law related to corruption by comparing the previous Corruption Law with the new Criminal Code. This study uses a normative legal approach method, qualitative descriptive research specifications, literature study data collection methods and qualitative data analysis methods. The results of this study are that the reform of criminal law is expected to increase the effectiveness of corruption eradication, but the new Criminal Code raises concerns. The reduction in the threat of punishment and the elimination of several important articles in the Corruption Law have the potential to reduce the effectiveness of corruption eradication. In addition, the reduction in fines and additional criminal penalties and the inconsistency with the Constitutional Court Decision No. 31/PUU-V/2012 can weaken efforts to eradicate corruption. Thus, legal reform through the new Criminal Code needs to be evaluated to ensure that these steps truly support effective corruption eradication.